2014
DOI: 10.7314/apjcp.2014.15.7.3293
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of α-Pinene on Hepatoma Carcinoma Cell Proliferation

Abstract: Background: Pine needle oil from crude extract of pine needles has anti-tumor effects, but the effective component is not known. Methods: In the present study, compounds from a steam distillation extract of pine needles were isolated and characterized. Alpha-pinene was identified as an active anti-proliferative compound on hepatoma carcinoma BEL-7402 cells using the MTT assay. Results: Further experiments showed that α-pinene inhibited BEL-7402 cells by arresting cell growth in the G2/M phase of the cell cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Alpha-pinene from a steam distillation extract of pine needles exhibits anti-proliferative effect on human hepatocellular carcinoma BEL-7402 cells by arresting cell cycle at the G2/M phase, downregulating CDC25C expression, while reducing CDK1 activity [241]. Rocaglamide-A (Roc-A), a natural anticancer compound from Aglaia , induces a rapid phosphorylation of CDC25A and its subsequent degradation, thereby blocking cell cycle progression of tumor cells at the G1-S phase [242].…”
Section: Cell Cycle Regulation By Natural Compounds Affecting Other Ementioning
confidence: 99%
“…Alpha-pinene from a steam distillation extract of pine needles exhibits anti-proliferative effect on human hepatocellular carcinoma BEL-7402 cells by arresting cell cycle at the G2/M phase, downregulating CDC25C expression, while reducing CDK1 activity [241]. Rocaglamide-A (Roc-A), a natural anticancer compound from Aglaia , induces a rapid phosphorylation of CDC25A and its subsequent degradation, thereby blocking cell cycle progression of tumor cells at the G1-S phase [242].…”
Section: Cell Cycle Regulation By Natural Compounds Affecting Other Ementioning
confidence: 99%
“…In previous study, we found that pine needle oil exhibited significant inhibitory effect on hepatoma carcinoma BEL-7402 cells in vitro and discussed the mechanism preliminarily (7).…”
Section: Introductionmentioning
confidence: 96%
“…ECG is rich in essential oil, and limonene, α‐pinene, and myrcene are its main components, accounting for up to 70% (Li et al., ; Lin, Chen, Tu, & Liu, ). Studies have shown that limonene has anti‐inflammatory effects and can also be used to eliminate phlegm (Wang, ), and α‐pinene has been shown to have antitumor and antioxidant activities and is also an important synthetic raw material (Chen et al., ; Yang, Tang, & Chen, ). Essential oil has aromatic, anti‐inflammatory, antibacterial, and antioxidant effects (Huang, Gu, & Li, ), thus it has important application prospects in the pharmaceutical industry and for the preparation of spices and flavorings.…”
Section: Introductionmentioning
confidence: 99%